Comparative Treatment Outcomes of Acute Manic Episodes with Antipsychotic Monotherapy Versus Combination Therapy with Mood Stabilizers: A Quasi-Experimental Study - Zia, Maria; Shoaib , Ahmed; Siab, Syeda Rabbia; Adnan, Rabiya; Zahra, Sana; Farid, Ishel (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the comparison in effectiveness of monotherapy (Antipsychotic) versus combination therapy (antipsychotic with mood stabilizer) in acute mania.Study Design: Quasi-Experimental study.Place and Duration of Study: Department of Psychiatry, Armed Forces Institute of Mental Health, Rawalpindi, Pakistan, from Dec 2024 to Nov 2025.Methodology: One hundred sixty patients aged 18-65 years, diagnosed with acute manic episode, having a baseline Young Mania Rating Scale (YMRS) score ≥ 20 at presentation, were included. The severity of mania was assessed using the Young Mania Rating Scale (YMRS) at baseline. Patients were allocated into two groups: Group-A (antipsychotic monotherapy) and Group-B (combination of antipsychotic plus mood stabilizer). At discharge, the YMRS score was reassessed to determine symptom improvement. Intergroup comparisons and logistic regression analysis were done.Results: A total of 160 patients with acute manic episodes were enrolled in a 1:1 ratio. Baseline Median YMRS was 32.00 (15.00) in Group-A and 32.50 (12.00) in Group-B (p=0.91). Median YMRS decreased from 32.00 (15.00) to 22.00 (8.00) in Group-A and from 32.50 (12.00) to 19.00 (7.00) in Group-B. The reduction in YMRS (Δ) was greater with combination therapy 14.00 (5.00) vs 9.50 (6.00) with a significant between-group difference (both discharge scores and Δ: p